High dielectric constant observed in (1 - x)Ba(Zr 0.07Ti 0.93)O 3-xBa(Fe 0.5Nb 0.5)O 3 binary solid-solution - Kruea-In C. (2014)
Binary solid-solutions of the (1 - x)Ba(Zr 0.07Ti 0.93)O 3-xBa(Fe 0.5Nb 0.5O 3) system, with 0.1 ≤ x ≤ 0.9,were fabricated via a solid-state processing technique. X-ray diffraction analysis revealed that all samples exhibited a single perovskite phase. The BaFe 0.5Nb 0.5O 3 also promoted densification and grain growth of the system. Dielectric measurements showed that all samples displayed a relaxor like behavior. The x = 0.1 sample presented a dielectric-frequency and temperature with low loss tangent (<0.07 at 10 kHz). For x > 0.2 samples, the dielectric data showed a broad dielectric constant-temperature curve with a giant dielectric characteristic. In addition, a high dielectric constant > 50,000 (at 10 kHz and temperature > 150 °C) was observed for the x = 0.9 sample. © 2012 Published by Elsevier Ltd.